Factors for a succesful education in occupational safety and health in schools: Contributions from teachers in Andalusia (Spain) - Burgos Garcia, Antonio; Rodriguez Sabiote, Clemente; Alvarez Rodriguez, Jose (Education Policy Analysis Archives, 2011)
In this research, we try to determine the influence of a set of success factors on the process of mainstreaming occupational safety and health in school. In the opinion of Andalusian teachers that were involved in an occupational safety and health program, these success factors produce benefits and advantages in the future jobs of students. We have developed a predictive-correlational study with a sample of teachers (N=258) who participated in the educative program: “Aprende a crecer con seguridad, 2009” (Regional Government of Andalusia -Department of Employment and Education-). Teachers evaluated a set of success factors (predictors) based on the model proposed by the European Agency for Safety and Health at Work (EU-OSHA). The results obtained from a multiple linear regression analysis indicate that factors related to "realization" and "decisions" are the most important predictors of success in acquiring benefits related to the future development of a job by students.